Efektivitas Edukasi Keluarga Berencana dalam Meningkatkan Pengetahuan dan Sikap Pasangan Usia Subur - Juwita; Nurhaeda (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2026)
Family Planning (FP) is one of the strategic efforts to improve the quality of maternal and child health and to control population growth. This study aims to determine the effectiveness of family planning education in improving the knowledge and attitudes of couples of reproductive age. This research employed a quasi-experimental design with a pre-test and post-test approach. The sample consisted of 50 respondents selected using purposive sampling technique. The instruments used were questionnaires measuring knowledge and attitudes. The results showed a significant increase in respondents' knowledge and attitudes after receiving family planning education (p < 0.05). Health education has proven to be effective in improving understanding and fostering positive attitudes toward family planning programs. It is recommended that health workers increase the intensity of educational interventions to support the success of family planning programs.